Identify The Relationship Between Suggestibility and Teaching Efficiency Among University Lecturers from Students’ Views at University of Zakho (Raparin Journal of Humanities (RJH), 2025)
The current research aims to identify the susceptibility to luring and its relationship to the teaching competence of university teachers from the point of view of students at the University. And to identify the significant differences between the students’ scores on the susceptibility to luring scale according to the variable of gender and academic stage. Is there a direct correlation between the susceptibility to luring and the teaching competencies of the university teacher from the point of view? View of University students. To indicate the aims of the study researchers relied on the scale of ( Hamza، 2016 ) about suggestibility consists (28) items about suggestibility and (24) items are divided into two fields first، (12) for teaching efficiency and (12) for personality efficiency. SPSS was used to find the results of the study. The finding of the study indicated that the lecturers’ performance was low according student's viewpoint at University. There was statistically no difference according to gender and specialization just there was statistically different according to grade and the level was higher among forth year grade. Finally، according to the results of the study the researcher is given several implications and suggestions for further studies.